Extremism, Free Speech and the Rule of Law: Evaluating the Compliance of Legislation Restricting Extremist Expressions with Article 19 ICCPR. Issue 85 (31st August 2017) - Shepherd, Amy
In the years since 9/11, international security discourse has heightened concerns around extremism, positioning this as the key threat that States need to address in order to prevent and combat terrorism. Politically, enactment of domestic legislation curtailing extremist expressions has been internationally authorised and encouraged and in May 2016 the United Kingdom ('UK'), spearheading a liberal State trend towards rights-restrictive approaches to extremism, announced its intention to enact legislation imposing a range of civil sanctions on those publicly expressing extremist views. But laws such as this restrict the core democratic right to freedom of expression and so must comply with the tripartite requirements for restrictions enshrined in Article 19(3) of the International Covenant on Civil and Political Rights ('ICCPR') to be legitimate. Using the UK to dynamically exemplify the issues, this paper assesses the manner in which the laws curtailing extremist expressions comply with international human rights law.